Peran Struktur Tata Kelola dalam Mencegah Kecurangan Internal di Perbankan Indonesia - Hartanto, Rudy; Sukarmanto, Edi; Rahayu, Dwi; Aulia, Asti Taskiyatul; Puspita, Nadiya Dwi (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2024)
The banking industry is an industry that has the most vulnerable impact on fraud. Internal fraud committed by the internal banking parties can have a impact on reputation of the banking bank itself. the purpose of this research is to examine the components of the banking management structure which consists of independent audit committees, risk management committees, audit audits of internal audit work units, and the size of the company's internal fraud. The population in this study were all banks in Indonesia from 2020 and 2021. The sample obtained in this study was 61 banks. The testing technique in this study is to use multiple regression analysis. The results showed that the independent audit committee and the Risk Management Committee had no effect on internal fraud. Whereas audit examination of internal audit work units and company size affects internal fraud. The test results show that banks must pay attention to the structure of corporate governance, especially the internal audit work unit and company size in terms of management to reduce the possibility of internal fraud.